Conocimiento y práctica del personal de enfermería sobre el proceso de esterilización a vapor en central de esterilización del Hospital Regional de Loreto 2021 - García Gonzales, Cecilia (2023)
The objective of the research was to determine the relationship that exists between the knowledge and practice of nursing staff on the steam sterilization process in the sterilization center of the Regional Hospital of Loreto, Punchana 2021. The population consisted of 40 people from the service Central Sterilization. The methodology applied in the research was basic with a quantitative approach and a non-experimental, cross-sectional design with a correlational scope. The technique that was applied was the survey and the observation and the instruments were the knowledge questionnaire about the steam sterilization process and the Checklist or observation. For data processing, the SPSS 26 program was used and descriptive statistics were applied for the univariate analysis and inferential statistics for the bivariate analysis. According to the results obtained, 90.0% (n=36) of the nursing staff presented a high level of knowledge and 10.0% (n=4) a medium level of knowledge, 10.0% (n=4) of they had inadequate practices and 90.0% (n=36) correspondingly adequate practices. The study concluded that there is a significant relationship between the level of knowledge and the practice of the nursing staff on the steam sterilization process in the sterilization center of the Regional Hospital of Loreto (Rho= 0.741**; α=0.000**, Sig. < 0.01) and there is a statistically significant relationship between the variable Level of knowledge and the dimensions of the steam sterilization process: sterilization method, sterilization process and disinfection process (rs=0.390*; Sig. < 0.05; rs=0.469* *; Sig. < 0.01; rs=0.432**; Sig. < 0.01).